PROFIL KREATIVITAS SISWA SMP DALAM MEMECAHKAN MASALAH MATEMATIKA DITINJAU DARI GAYA BELAJAR - Warli Warli; Puji Rahayu; Siti Ariyanti (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2019)
This study aims to describe the profile of junior high school students' creativity in solving mathematical problems in terms of learning styles. The type of this research is descriptive qualitative. Research subjects are junior high school students with visual, auditory, and kinesthetic style. Research subjects were 6 students, consisting of 2 students in visual learning style, 2 auditorially-style students, and 2 students of kinesthetic learning style. The results of research are as follows: The visual creativity profile of the students in visual learning style tends to be low in solving math problems. Audience-style student creativity profiles tend to be high in solving mathematical problems. And the students' creativity profile with kinesthetic learning tends to be very low in solving math problems.